2021
DOI: 10.1097/inf.0000000000003418
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Balamuthia mandrillaris Cerebral Abscess in a Pediatric Patient With Complete Surgical Resection and Antimicrobial Therapy

Abstract: Cerebral amebic encephalitis due to Balamuthia mandrillaris is a rare yet typically fatal disease. As such, identification of the clinical characteristics, appropriate diagnostic workup and commencement of treatment is frequently delayed. Here, we present a case of a 4-year-old male with a B. mandrillaris cerebral abscess successfully treated with expedited neurosurgical resection and broad-spectrum antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A previous study examined the effects of the conjugation of amphotericin B on N. fowleri, revealing encouraging results; however, in this study, silver nanoparticles were utilized for the conjugation, and the cytotoxicity of the compounds alone was not evaluated [ 8 ]. Furthermore, until now, conjugated curcumin and amphotericin B have not been evaluated on B. mandrillaris , for which the number of reported cases is evident [ 45 , 46 , 47 ]. The nanocarriers utilized in this study also revealed greater drug loading efficiency, thus showing their capability for higher drug release to the desired target site [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examined the effects of the conjugation of amphotericin B on N. fowleri, revealing encouraging results; however, in this study, silver nanoparticles were utilized for the conjugation, and the cytotoxicity of the compounds alone was not evaluated [ 8 ]. Furthermore, until now, conjugated curcumin and amphotericin B have not been evaluated on B. mandrillaris , for which the number of reported cases is evident [ 45 , 46 , 47 ]. The nanocarriers utilized in this study also revealed greater drug loading efficiency, thus showing their capability for higher drug release to the desired target site [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 A small proportion of patients were diagnosed by CSF analysis or skin biopsy. We have summarized previous reports of B. mandrillaris encephalitis survivors 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Table 2). Most of the survivors were diagnosed by early brain biopsy within 1 week of admission or by biopsy of preceding skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is no specific drug targeting B. mandrillaris . Current treatments for GAE rely primarily on trial combinations of antimicrobial and antifungal drugs, resulting in variations in clinical outcomes ( Doyle et al, 2011 ; Cuoco et al, 2022 ). Thus, the development of more effective drugs remains a topic of intensive research ( Phan et al, 2021 ; Ferrins et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%